The viability of small-scale farming at the Tyhefu Irrigation Scheme, Eastern Cape - Sishuta, Happy Babalwa (Rhodes University, Faculty of Humanities, Department of Sociology and Industrial Sociology, 2004)
This investigation is conducted against the background of current attempts to rehabilitate and revive the now defunct Tyhefu irrigation scheme. The poor track record of many irrigation schemes (despite huge investments) in the former homelands has prompted the government to reconsider its active and direct role in small-scale irrigation farming. This has resulted in the closure of many irrigation schemes including Tyhefu irrigation scheme. The new policy framework in South Africa, known as the irrigation management transfer, is premised on the transfer of ownership, authority and responsibility of small-scale irrigation schemes from government to the farmers. Tyhefu irrigation scheme was a state-driven, top-down initiative. This study argues that the justifications for the Tyhefu irrigation scheme were conflated, with the result that the need for political control of the Tyhefu area far outweighed the considerations regarding the financial viability and sustainability of the proposed project. Given the repressive political climate of the time in South Africa, the planners' proposals were a mechanism for the realization of the socio-political and economic agendas of the apartheid state and Ciskei government. Although technical factors critical for project success were examined, little or no attention was paid to the socio-economic aspects. For the planners, the main requirements for success entailed centralized managerial control, no participation of the beneficiaries, capital intensive and sophisticated agricultural techniques and the production of high value crops. Therefore, it can be argued that the nature of the planning and implementation of the Tyhefu irrigation scheme was ill-conceived, short-sighted and misguided. A review of the literature on irrigation development on the African continent provided useful insights for this study. The lessons from irrigation development experience in Sub-Saharan Africa indicate that the continent is littered with examples of derelict and costly failures. What stands out in many of these irrigation projects is their over-emphasis on technical issues to the complete neglect of human and other social aspects. Working partnerships between the farmers and irrigation scheme management could, thus, not be realized. Almost without exception the case studies used here indicate that the industrious type of farmer was never developed as was envisioned in the planning documents. Neither were rural livelihoods improved in a sustainable manner. The findings of this study suggest that irrigation management transfer is a complex and delicate process. In this new set of arrangements, beneficiaries face formidable challenges in terms of capacity (human and financial) if small-scale irrigation farming is to become a viable sector. No doubt, the viability and sustainability of the Tyhefu irrigation scheme demands a comprehensive package of interventions that address various issues of markets and marketing, capital investment and access to finance, technology, education and training, support and extension services. It is evident that institutional aspects and the related issue of functional literacy require much more attention than thus far. As a result, at the moment there is no possibility for independent agricultural production.,KMBT_363
Keywords: Farms, Small -- South Africa -- Eastern Cape; Irrigation -- South Africa -- Eastern Cape; Irrigation farming -- South Africa -- Eastern Cape